The Role of Debt Covenants in Assessing the Economic Consequences of Limiting Capitalization of Exploration Costs. - Barrett, M. Edgar; Frost, Carol A.; Bernard, Victor L. (The Accounting Review, 1989)
ABSTRACT: Several studies have hypothesized that economic consequences of mandated accounting procedures arise through impacts on firms' accounting-based loan covenants. However, this research has involved very little direct examination of the loan contracts. This study directly examines how public and private loan agreements were affected by an accounting procedure mandated by the SEC. It analyzes 24 loan agreements of 18 oil and gas firms that, as a result of an SEC requirement announced on May 6, 1986, recorded writeoffs of exploration costs for the first quarter of 1986. The principal finding is that, even for a mandated accounting procedure that caused both large financial statement differences and some technical violations of loan covenants, there were no observable economic consequences for the affected firms. This result casts doubt on the Importance of economic consequences of other mandated accounting procedures that might operate through affects on debt covenants.